Working Conditions of Support Services Professionals in School Integration Programs in Chile: A Mixed Methods Study - Dinamarca-Aravena, Katherine Andrea (Revista Chilena de Fonoaudiología, 2024)
In the context of educational inclusion, Chile stands out as one of the first countries to formalize the work of speech therapists, psychologists, physical therapists, and occupational therapists within school settings, known as Support Services Professionals. This research analyzes the perceptions of these professionals regarding their working conditions in School Integration Programs (PIE) in Chile. A sequential, exploratory, and mixed-methods approach was used. Interviews were carried out (N=52) and a questionnaire was administered (N=474) using the Respondent Driven Sampling (RDS) method. The interviews were analyzed using a thematic approach, while descriptive statistics were used to analyze quantitative results. The results reveal that formalizing the working conditions of Support Services Professionals contributes to their retention in schools. However, the lack of adequate working spaces, the restriction and standardization of time allocated for intervention, and insufficient resources negatively impact educational practice and contribute to burnout. The tensions highlighted by the professionals underscore the urgency of investigating the management of resources allocated to the development of PIEs. This research is pioneering in its subject matter and provides, for the first time in the country, a detailed description of the working conditions of Support Services Professionals. It also demonstrates the implementation of a non-conventional sampling method, which could be of interest to researchers addressing hard-to-reach populations or those without an established sampling frame. The findings invite policymakers, researchers, and civil society to reflect on the working conditions in schools and to assess the efficiency with which resources are utilized in the country’s PIEs.